LOCOMOTION IN DERIVED DICYNODONTS (SYNAPSIDA, ANOMODONTIA): A FUNCTIONAL ANALYSIS OF THE PELVIC GIRDLE AND HIND LIMB OF TETRAGONIAS NJALILUS - Fröbisch J. (My University, 2006)
A general locomotor model for derived dicynodont anomodonts is proposed on the basis of a functional analysis of the pelvic girdle and entire hind limb of the medium-sized Middle Triassic dicynodont Tetragonias njalilus. The joint mobility of the hind limb is examined, and a hind limb step cycle is reconstructed. The data provided in this case study indicate that Tetragonias adopted a highly adducted (upright) hind limb posture during stance and most of its stride. Nevertheless, lateral undulation of the vertebral column must also have contributed to the locomotion of dicynodonts. Character optimization of the traits associated with an upright posture of the hind limb shows a gradual evolution of dicynodont locomotion. The evolution of an upright hind limb posture has occurred several times independently in a number of amniote clades. Within synapsids, the Anomodontia, Dinocephalia, and Theriodontia acquired a parasagittal hind limb gait already as early as the late Paleozoic and early Mesozoic, prior to its evolution in mammals. This phenomenon has previously been explained as being related to an increase in body size as a response to increased biomechanical stress on the limb. This scenario appears plausible with respect to dicypodonts because of the occurrence of megaherbivore-sized taxa in the Triassic, but this study shows that a parasagittal gait had already evolved in the medium-sized basal kannemeyeriiform Tetragonias. Therefore, the vertical support of the body by the hind limbs in medium-sized dicynodonts could have allowed the evolution of the large Triassic taxa in the first place. © 2006 NRC Canada.
Keywords: Мезозой::Триасовая; Mesozoic::Triassic